Better campus life for visually impaired University students: intelligent social walking system with beacon and assistive technologies - Kose, U. (Springer, 2020)
Objective of this study is to introduce a novel, low-cost intelligent social walking path support system for visually impaired students in a wide campus area, by employing beacons, optimization based Artificial Intelligence techniques, Big Data support, and a system rising over Internet of Things. In detail, the developed system has been used within two connected campus areas of Suleyman Demirel University located in the city of Isparta in Turkey and an effective walking path support was ensured for enabling visually students to go target locations with instructions given by an intelligent system. In this way, it is also aimed to enable students to experience a better campus life. The study done here is unique with its Artificial Intelligence oriented characteristics ensuring an intelligent navigation control and planning system by benefiting from only interactions among beacons and mobile devices as not requiring to use physical road bumps, so lowering costs by eliminating both physical components and advanced communication systems. Also, other studentsâ data over social media environments are used as Big Data to support effective decisions taken by the system. After real implementation of the system, too much positive feedback was obtained from visually impaired students. Â© 2018, Springer Science+Business Media, LLC, part of Springer Nature.